Re-explore the viability and authenticity of Gallup workplace audit in private university - Khanna, Ruchi (Business, Management and Economics Engineering, 2020)
Purpose – Employee productivity is directly affected by the employee engagement. Researchers have continuously been focused on whether people working in the organisation are satisfied with the work or not. The Gallup 12 Workplace Audit is an instrument used to measure employee engagement. The purpose of this study is to re-explore the viability of this instrument in an educational context. The secondary objective of this study is to find out if The Gallup Work Audit instrument, which is an international survey, can be used in the educational sector in the context of India for measuring faculties’ engagement.Research methodology – A cross-sectional analysis with grab sampling was used. Descriptive statistics, such as frequency counts, were used to describe the sample. Acceptable internal consistency was reached through exploratory factor analysis.Findings – First results showed that none of the items needed to be eliminated from the scale and that the scale had very high reliability. Acceptable internal consistency was reached through an exploratory factor analysis which resulted in a one-factor model of work engagement.Research limitations – The data collection for the study was limited to one major university, therefore generalisation the results must be done with great care.Implications – This study helps universities to identify their critical drivers of employee engagement, and gives them a clear understanding of their construct.Originality – This study is one of the first attempts to re-explore the viability and authenticity of Gallup Workplace Audit in educational institution (university level).